2019
DOI: 10.1002/msc.1424
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low back pain beliefs and management practices in Africa: Time for a rethink?

Abstract: Background: Chronic low back pain (CLBP) beliefs are important psychosocial risk-factors affecting the occurrence and progression of CLBP. To address pain beliefs and implement recommended biopsychosocial approaches for CLBP management, an understanding of patients' and healthcare professionals' (HCPs') beliefs, as well as CLBP management practices, is necessary. A narrative review was conducted to explore CLBP beliefs and practices in African countries.Methods: Two systematic searches were conducted using sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…For instance, beliefs about LBP may be under-reported in the African settings due to cultural or religious reasons. Although, patient beliefs and other psychosocial factors influences LBP in comparable ways both in the developed and developing countries [38], culture can mediate how these beliefs and psychosocial factors are expressed. Thus, the difference in the factor structures of the different versions of the BBQ may be adduced to the differences in culture.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, beliefs about LBP may be under-reported in the African settings due to cultural or religious reasons. Although, patient beliefs and other psychosocial factors influences LBP in comparable ways both in the developed and developing countries [38], culture can mediate how these beliefs and psychosocial factors are expressed. Thus, the difference in the factor structures of the different versions of the BBQ may be adduced to the differences in culture.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 systematic review (6 studies) found that management pathways in African countries typically favour treatment approaches with ineffective passive treatment modalities. 1 The authors identify a need for culturally sensitive and context-specific biopsychosocial interventions. A 2020 survey of physiotherapists in Nigeria found that although 79% were aware of clinical practice guidelines for treatment of low back pain, just 28% reported adhering to these when treating people with low back pain.…”
Section: Many Patients With Low Back Pain Are Still Receiving the mentioning
confidence: 99%
“…All healthcare professionals reported providing predominantly biomedically orientated care, a finding found in other low-and middleincome countries (Ahenkorah et al, 2019;Mousavi et al, 2011).…”
Section: Biomedical Model Of Carementioning
confidence: 68%